Nursing of a patient with post-stroke constipation of Qi-deficiency type treated by Baliao acupoints moxibustion and acupuncture combined with oral administration of Yiqi Runchang decoction (灸八髎穴联合内服益气润肠中药汤剂治疗1例中风后气虚便秘患者的护理体会) - LI Juan (李娟); FENG Ruiping (冯瑞萍); LI Ling (黎玲) (中西医结合护理)
This paper summarized the Nursing of a patient with post-stroke constipation of Qi-deficiency type treated by Baliao acupoints moxibustion and acupuncture combined with oral administration of Yiqi Runchang decoction. A comprehensive assessment of nursing risk was carried out before treatment. Traditional Chinese Medicine external treatment such as moxibustion and acupuncture at Baliao acupoints were performed to improve the recovery of intestinal function. The patient received oral administration of Yiqi Runchang decoction to regulate the body constitution. In addition, a prescription of drinking habits was administrated to promote defecation, and other interventions such as dietary guidance, exercise and emotion care were carried out to relieve the symptoms of Qi-deficiency syndromes. (本文总结灸八髎穴联合内服益气润肠中药汤剂治疗1例中风后气虚便秘患者的护理体会。在完善护理评估的基础上, 遵医嘱给予八髎穴艾灸、针灸等中医外治疗法, 以增强肠道蠕动, 缓解便秘; 给予益气润肠中药汤剂内服, 从根本上调理; 同时基于子午流注理论, 为患者开具饮水处方, 以软化粪便, 促进胃肠蠕动, 利于排便; 结合患者的疾病特点予以饮食调护、运动疗法和情志护理。经过10 d中医内服外用联合治疗以及辨证施护, 患者气虚便秘症状得到有效改善。)